From 'me' to 'we': negotiating new family identity through meal consumption in Asian cultures. Issue 4 (14th September 2015) - Edirisingha, Prabash Aminda; Ferguson, Shelagh; Aitken, Rob
Abstract : Purpose: – The purpose of this paper is to develop a conceptual framework which deepens our understanding of identity negotiation and formation in a collectivistic Asian context. Drawing from a three-year, multi-method ethnographic research process, the authors explore how contemporary Asian consumers construct, negotiate and enact family identity through meal consumption. The authors particularly focus on the ways in which Asian consumers negotiate values, norms and practices associated with filial piety during new family formation. Building on the influential framework of layered family identity proposed by Epp and Price (2008), the authors seek to develop a framework which enables us to better understand how Asian consumers construct and enact their family identity through mundane consumption. Design/methodology/approach: – As most of the identity negotiation in the domestic sphere takes place within the mundanity of everyday life, such as during the routines, rituals and conventions of "ordinary" family meals, the authors adopted an interpretive, hermeneutic and longitudinal ethnographic research approach, which drew from a purposive sample of nine Sri Lankan couples. Findings: – The authors present the finding in three vivid narrative exemplars of new family identity negotiation and discuss three processes which informants negotiated the layered family identity. First, Asian families negotiate family identity by re-formulating aspects of their relational identity bundles. Second, re-negotiating facets of individual identity facilitates construction of family identity. Finally, re-configuring aspects of collective family identity, especially in relation to the extended family is important to family identity in this research context. The authors also propose filial piety as a fundamental construct of Asian family identity and highlight the importance of collective layer over individual and relational family identity layers. Research limitations/implications: – The aim of this paper is to develop a conceptual framework which deepens our understanding of identity negotiation and formation in a collectivistic Asian context. Even though exploring Sinhalese, Sri Lankan culture sheds light on understanding identity and consumption in other similar Asian cultures, such as Indian, Chinese and Korean; this paper does not suggest generalisability of findings to similar research contexts. On the contrary, the findings aim to present an in-depth discussion of how identities are challenged, negotiated and re-formulated during new family formation around specific consumption behaviours associated with filial piety in a collectivistic extended family. Social implications: – As this research explores tightly knit relationships in extended families and how these families negotiate values, norms and practices associated with filial piety, it enables us to understand the complex ways in which Asian families negotiate identity. The proposed framework could be useful to explore how changing social dynamics challenge the traditional sense of family in these collectivistic cultures and how they affect family happiness and well-being. Such insight is useful for public policymakers and social marketers when addressing family dissatisfaction–based social issues in Asia, such as increasing rates of suicide, divorce, child abuse, prostitution and sexually transmitted disease. Originality/value: – Little is known about the complex ways in which Asian family identities are negotiated in contrast to Western theoretical models on this topic. Particularly, we need to understand how fundamental aspects of Asian family identity, such as filial piety, are continuously re-negotiated, manifested and perpetuated during everyday life and how formulations of Asian family identity may be different from its predominantly Western conceptualisations. Therefore, the paper provides an adaptation to the current layered family identity model and proposes filial piety as a fundamental construct driving Asian family identity.